APPLICATION OF BLOCKCHAIN AND SMART-CONTRACT ON WAQF ASSET MANAGEMENT: IS IT NECESSARY? - Agus Setiawan; Mohamad Soleh Nurzaman (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Waqf assets are assets that can be utilized for the benefit of the people. Currently, there are many waqf asset management using internet-based Waqf Information Systems. However, the database used by the system is generally centralized, so it is prone to data manipulation. Each waqf entity has its data, causing data differences between waqf entities. This study aims to provide the concept of waqf asset management using Blockchain technology and Smart Contracts. The method is a qualitative analysis method with secondary data from various kinds of literature, study journals, and reports published by the government and related agencies. This study concludes that the concept of waqf asset management based on Blockchain technology and Smart contracts can facilitate the management of waqf assets, both movable and immovable assets. In addition, it can increase data transparency between nadzhir, wakif, and waqf regulators and minimize data manipulation. The role of regulators such as the Ministry of Religion, BWI, and BI is needed to create regulations that support the implementation of waqf management based on Blockchain technology and Smart Contract.